Spectrophotometric Determination of Flurbiprofen Sodium in Biological Fluid - CHAUHAN, C.S.; SINGHVI, I.; CHOUDHURY, P.K. (Asian Journal of Chemistry, 2010)
Simple and sensitive UV spectrophotometric method has been developed for estimation of flurbiprofen sodium in urine. The developed method is based on extraction of drug from urine sample using chloroform after proper treatment. The chloroform extract shows absorbance maxima at 256 nm and obeys Beer's law in the concentration range of 2-12 μg/mL of drug. No interference was observed from the common metabolites present in the urine after proper extraction.